Outcome of early surgery in infantile esotropia: Our experience in tertiary care hospital - Singh, Anirudh (Med J Armed Forces India, 2017)
BACKGROUND: Infantile esotropia is a convergent strabismus presenting before 6 months of age and is the most common strabismus disorder presenting in the ophthalmology OPD. The dilemma of whether to go for early surgery and how early has been a matter of research for the last 50 years. We describe our results of surgery in infantile esotropia at variable age groups, as well as with different reoperation rates and compare with the results in western literature. METHODS: A prospective study was carried out through a review of 113 cases operated for infantile esotropia between February 2013 and August 2014. The variables studied were: age at surgery, type of fixation, refractive error, associated nystagmus, inferior oblique overaction or dissociated vertical deviation (DVD), type of surgery performed and pre- and postoperative deviation angles. RESULTS: There were 67 male and 46 female cases of infantile esotropia. The age group of patients varied from 6 months to 12 years. Latent nystagmus was seen in 22 cases, inferior oblique overaction in 49 cases and DVD (mild) in 14 cases. Bimedial rectus recession was done in 78 cases and recession–resection in non-dominant eye in remaining 35 cases. The postoperative residual deviation was <10 PD in 102 cases, between 10 and 16 PD in 5 cases and more than 16 PD in 6 cases. Only 6 cases (5.3%) required reoperation for correction of residual deviation. CONCLUSION: The authors recommend surgery before 12 months in all cases of infantile esotropia. The reoperation rates in the current study were considerably low.